PENGARUH SISTEM PENGENDALIAN INTERN, KEMAMPUAN SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI PADA KUALITAS LAPORAN BARANG MILIK DAERAH - Subrata, I Wayan; Yasa, Gerianta Wirawan; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This research aimed to get empirical evidence of the effect of the internal control system, human resource ability and information technology utilization on quality of local government assets report. The amount of samples in this research were 42 work units (SKPD) on Gianyar local government, that selected by purposive sampling method. The data about internal control systems, human resource ability and information technology utilization was collected by the use of questionnaire, while the data about quality of local government assets report was collected by evaluate the compliance level of assets report with established criteria based Permendagri No. 17 in 2007. The analysis technique used is multiple linear regression analysis. The result of analysis showed that the internal control system, human resource ability and information technology utilization has positive effect on quality of local government assets report.
Keywords: quality of assets report, internal control systems, human resource ability, information technology utilization